Inter-observer concordance in normal and pathological findings of the hip joint in plain radiographs. - Atria, Maria Giovanna; Calvi, Marco; Zorzetto, Giada; Curti, Marco; Celentano, Angelica; Duvia, Marta; Venturini, Massimo; Genovese, Eugenio Annibale (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The purpose of the study was to compare the data obtained by two independent observers and statistically analyze the results using Cohen’s K to highlight the concordance or discordance in the diagnosis of normality, pathology and, in particular, the type of femoro-acetabular impingement (FAI) on plain films.Methods: the study was conducted retrospectively. The only inclusion criterium was the minimum age of 20 years. All patients underwent a radiographic examination of the pelvis in standard anteroposterior projection in orthostasis.Results: A good concordance between the two operators in the examination of normal hip joint (k= 0.68 right/ 0,74 left) was found; a similar grade of agreement was found for the analysis of “pincer” type FAI (k = 0.73 right, 0,67 left). The best results in concordance were achieved in the examination of “cam” type FAI (k= 0.82 right, 0,88 left), “mixed” type FAI (k = 0.85 right, 0,86 left), and in findings of “coxa profunda” (k = 0.92 right, 0,88 left).Conclusion: We found a good concordance between the two readers; a few cases of disagreement were found in the diagnosis of "pincer" type FAI and absence of disease. This discrepancy may be due to the different weight given by the single observer to the clinical indication that leads the patient to examination, but also by the difficulty of a not dedicated radiologist to show some subtle signs indicative of early FAI.